2022
DOI: 10.3390/nano12122079
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an Efficient N, S Co-Doped WO3 Operated in Wide-Range of Visible-Light for Photoelectrochemical Water Oxidation

Abstract: In this work, a highly efficient wide-visible-light-driven photoanode, namely, nitrogen and sulfur co-doped tungsten trioxide (S-N-WO3), was synthesized using tungstic acid (H2WO4) as W source and ammonium sulfide ((NH4)2S), which functioned simultaneously as a sulfur source and as a nitrogen source for the co-doping of nitrogen and sulfur. The EDS and XPS results indicated that the controllable formation of either N-doped WO3 (N-WO3) or S-N-WO3 by changing the nW:n(NH4)2S ratio below or above 1:5. Both N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Particularly, the vibrational peaks at 127 and 179 cm –1 are the lattice modes corresponding to the (W 2 O 2 )­n chains . Whereas the peaks appearing in pairs at 266 and 320 cm –1 result from the bending reverberation of the bridging oxygens (δ W–O–W ) . And the other two pairs of peaks with peak broadening at 711 and 801 cm –1 are the distinctive characteristic Raman modes of the monoclinic phase WO 3 crystallites and arising from the stretching vibration of the bridging oxygens (ν W–O–W ) .…”
Section: Transmission Electron Microscopy (Tem and Hr-tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the vibrational peaks at 127 and 179 cm –1 are the lattice modes corresponding to the (W 2 O 2 )­n chains . Whereas the peaks appearing in pairs at 266 and 320 cm –1 result from the bending reverberation of the bridging oxygens (δ W–O–W ) . And the other two pairs of peaks with peak broadening at 711 and 801 cm –1 are the distinctive characteristic Raman modes of the monoclinic phase WO 3 crystallites and arising from the stretching vibration of the bridging oxygens (ν W–O–W ) .…”
Section: Transmission Electron Microscopy (Tem and Hr-tem)mentioning
confidence: 99%
“…55 Whereas the peaks appearing in pairs at 266 and 320 cm −1 result from the bending reverberation of the bridging oxygens (δ W−O−W ). 56 And the other two pairs of peaks with peak broadening at 711 and 801 cm −1 are the distinctive characteristic Raman modes of the monoclinic phase WO 3 crystallites and arising from the stretching vibration of the bridging oxygens (ν W−O−W ). 57 This appearance of a significant number of active Raman modes is attributed to the distortions in ReO 3 -type structure in original monoclinic phase, as the group theory suggests that two active modes must be demonstrated in this type of structure always.…”
Section: And Hr-tem)mentioning
confidence: 99%
“…Since TiO 2 was first reported as photoanode by Fujishima and Honda in 1972 [ 5 ], numerous semiconductors (WO 3 , Fe 2 O 3 , Ta 3 N 5 , TaON, etc.) have been employed for photoanode materials [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several impurity-doped oxides have shown that impurity doping can improve the conductivity and narrow band gap of oxide nanostructures; moreover, impurity doping can increase the roughness and active site number of nanostructures and improve the activity of photocatalysts. [15][16][17] Several works on synthesizing metaldoped WO 3 nanostructures demonstrate an enhanced photocatalytic activity compared to pristine WO 3 . The Nb-doped WO 3 nanoparticles have higher solar energy conversion efficiency than the pristine WO 3, thus enhancing photoactive properties.…”
mentioning
confidence: 99%
“…20 Notably, compared with metal doping, several examples of non-metallic doped oxides show better charge separation efficiency and higher efficiency in narrowing optical gaps, contributing to photoactivity enhancement. 15,17,21 Recently, sulfur atoms have been doped into oxide semiconductors with various methods to improve photocatalytic activity. For example, sulfur-doped TiO 2 through different chemical methods has been proposed to significantly enhance the photocatalytic activity compared with pristine TiO 2 .…”
mentioning
confidence: 99%